MY CRYSTAL MATH: ENHANCING NUMERACY AND BASIC OPERATIONS SKILLS IN AUTISTIC CHILDREN THROUGH MOBILE APPLICATIONS IN MATHEMATICS EDUCATION - Nur Atikah Mohd Roslan; Nurulhuda Zainuddin (Journal of Islamic, Social, Economics and Development, 2023)
Autism Spectrum Disorder (ASD) is a neurodevelopmental condition characterized by deficits in social interaction, communication challenges, and repetitive behaviors. These factors create significant challenges for individuals with autism, their families, and society at large. Particularly in the realm of social communication, autistic children struggle to form and maintain connections, relying on nonverbal cues such as facial expressions, gestures, and eye contact. Consequently, teaching mathematics to autistic children requires an innovative and tailored approach. The objective of this research is to develop a mobile application specifically designed to help autistic children learn numeracy and basic mathematical operations. The project follows the waterfall methodology, encompassing requirements gathering, analysis, design, and implementation phases to achieve its specific goals. The resulting mobile app provides a comprehensive learning experience, encompassing numeracy, addition, subtraction, and a final quiz to assess the understanding of autistic children as they engage with the interactive games. The developed mobile application serves as a valuable tool for teachers in effectively instructing and guiding autistic children in mathematics. Its tailored approach caters to the unique learning styles of autistic individuals, enhancing their interaction and overall educational experience. This application has the potential to become an invaluable resource, enabling autistic children to acquire foundational mathematical skills with greater ease and effectiveness.